FRI0613 H-ferritin and pro-inflammatory cytokines are increased in the bone marrow of adult patients affected by macrophage activation syndrome. (15th June 2017) - Ruscitti, P; Cipriani, P; Ciccia, F; Benedetto, P Di; Lizzi, AR; Liakouli, V; Berardicurti, O; Carubbi, F; Guggino, G; D'Andrea, G; Triolo, G; Giacomelli, R
Abstract : Background: During macrophage activation syndrome (MAS), an inflammatory life-threatening syndrome, extremely high levels of serum ferritin may be observed [1]. Ferritin is an intracellular iron storage protein comprising 24 subunits that may be divided in heavy (H) subunits and light (L) subunits, based on their molecular weight [2]. The H-/L-subunits ratio may change, depending on the specific tissue and the physiologic status of the cell. In the normal condition, ferritin enriched in L subunits (L-ferritin) has been found in the liver and in the spleen, whereas the ferritin enriched in H subunits (H-ferritin), may be mainly observed in the heart and kidneys [2]. Objectives: We investigated the tissue expression of both H-and L-ferritin as well as the macrophage subsets expressing these molecules, in the inflammatory BM infiltrate of MAS patients. In addition, the co-expression of IL-1β, TNF, IFN-γ and H- or L ferritin, within the inflammatory cells, was assessed. Finally, we explored if the imbalance between H-ferritin and L-ferritin as well as the number of ferritin positive cells may be considered helpful bio-markers to assess the severity of these patients. Methods: We analysed the bone marrow (BM) biopsies, by immunofluorescence of 10 adult MAS patients affected by rheumatic disease to assess the presence of: i. both H- and L-ferritin; ii. the number of CD68+/H-ferritin+ and CD68+/L-ferritin+; iii. the tissue pro-inflammatory cytokines, IL-1β, TNF, IFN-γ; and we correlated these data with clinical and laboratory data. Furthermore, the presence of ferritins was assessed in the sera of the same patients by western blot analysis. Results: We observed an increased tissue expression of H-ferritin and of pro-inflammatory cytokines (IL-1β, TNF, IFN-γ). Western blot analysis, in the sera, of H-ferritin mirrored data on the tissue. Furthermore, an increased number of CD68+/H-ferritin+ cells and an infiltrate of cells co-expressing H-ferritin and IL-12, suggesting an infiltrate of M1 macrophages, were observed. Tissue H-ferritin levels correlated with the decreased counts of WBC (p=0.01) and PLT (p=0.0001); with the increased values of serum ferritin (p=0.012) and C-reactive protein (CRP) (p=0.0058); and with the tissue expression of IL-1β (p=0.006). The number of the CD68+/H-ferritin+ cells correlated with the decreased counts of WBC (p=0.03) and PLT (p=0.0007), and with the increased serum ferritin levels (p=0.0088) and CRP (p=0.049). The analyses concerning tissues L-ferritin as well as the number of CD68+/L-ferritin+ cells and the same parameters failed to show any significant result. Conclusions: We observed an increased tissue expression of H-ferritin associated with an increased expression of IL-1β. Interestingly, in the BM inflammatory infiltrate an increased number of CD68+/H-ferritin+ cells was shown. Of note, tissue expression of H-ferritin as well as the number of CD68+/H-ferritin+ significantly were associated with the hematological involvement of the disease, suggesting possible bio-markers to assess the severity of these patients. References: Ramos-Casals M, et al. Lancet. 2014;383:1503–16. Rosário C, et al. BMC Med. 2013;11:185. Disclosure of Interest: None declared